Beyond cyanogenesis: Temperature gradients drive environmental adaptation in North American white clover ( Trifolium repens L.) - Wen‐Hsi Kuo; Limei Zhong; Sara J. Wright; David M. Goad; Kenneth M. Olsen (Molecular Ecology, 2024)
Species that repeatedly evolve phenotypic clines across environmental gradients have been highlighted as ideal systems for characterizing the genomic basis of local environmental adaptation. However, few studies have assessed the importance of observed phenotypic clines for local adaptation: conspicuous traits that vary clinally may not necessarily be the most critical in determining local fitness. The present study was designed to fill this gap, using a plant species characterized by repeatedly evolved adaptive phenotypic clines. White clover is naturally polymorphic for its chemical defence cyanogenesis (HCN release with tissue damage); climate‐associated cyanogenesis clines have evolved throughout its native and introduced range worldwide. We performed landscape genomic analyses on 415 wild genotypes from 43 locations spanning much of the North American species range to assess the relative importance of cyanogenesis loci vs. other genomic factors in local climatic adaptation. We find clear evidence of local adaptation, with temperature‐related climatic variables best describing genome‐wide differentiation between sampling locations. The same climatic variables are also strongly correlated with cyanogenesis frequencies and gene copy number variations (CNVs) at cyanogenesis loci. However, landscape genomic analyses indicate no significant contribution of cyanogenesis loci to local adaptation. Instead, several genomic regions containing promising candidate genes for plant response to seasonal cues are identified — some of which are shared with previously identified QTLs for locally adaptive fitness traits in North American white clover. Our findings suggest that local adaptation in white clover is likely determined primarily by genes controlling the timing of growth and flowering in response to local seasonal cues. More generally, this work suggests that caution is warranted when considering the importance of conspicuous phenotypic clines as primary determinants of local adaptation.

Genetic trade‐offs underlie divergent life history strategies for local adaptation in white clover - Sara J. Wright; David M. Goad; Briana L. Gross; Patricio R. Muñoz; Kenneth M. Olsen (Molecular Ecology, 2022)
Local adaptation is common in plants, yet characterization of its underlying genetic basis is rare in herbaceous perennials. Moreover, while many plant species exhibit intraspecific chemical defence polymorphisms, their importance for local adaptation remains poorly understood. We examined the genetic architecture of local adaptation in a perennial, obligately‐outcrossing herbaceous legume, white clover ( Trifolium repens ). This widespread species displays a well‐studied chemical defence polymorphism for cyanogenesis (HCN release following tissue damage) and has evolved climate‐associated cyanogenesis clines throughout its range. Two biparental F 2 mapping populations, derived from three parents collected in environments spanning the U.S. latitudinal species range (Duluth, MN, St. Louis, MO and Gainesville, FL), were grown in triplicate for two years in reciprocal common garden experiments in the parental environments (6,012 total plants). Vegetative growth and reproductive fitness traits displayed trade‐offs across reciprocal environments, indicating local adaptation. Genetic mapping of fitness traits revealed a genetic architecture characterized by allelic trade‐offs between environments, with 100% and 80% of fitness QTL in the two mapping populations showing significant QTL×E interactions, consistent with antagonistic pleiotropy. Across the genome there were three hotspots of QTL colocalization. Unexpectedly, we found little evidence that the cyanogenesis polymorphism contributes to local adaptation. Instead, divergent life history strategies in reciprocal environments were major fitness determinants: selection favoured early investment in flowering at the cost of multiyear survival in the southernmost site versus delayed flowering and multiyear persistence in the northern environments. Our findings demonstrate that multilocus genetic trade‐offs contribute to contrasting life history characteristics that allow for local adaptation in this outcrossing herbaceous perennial.

Hybridization, polyploidy and clonality influence geographic patterns of diversity and salt tolerance in the model halophyte seashore paspalum ( Paspalum vaginatum ) - David M. Goad; Ivan Baxter; Elizabeth A. Kellogg; Kenneth M. Olsen (Molecular Ecology, 2021)
In plant species, variation in levels of clonality, ploidy and interspecific hybridization can interact to influence geographic patterns of genetic diversity. These factors commonly vary in plants that specialize on saline habitats (halophytes) and may play a role in how they adapt to salinity variation across their range. One such halophyte is the turfgrass and emerging genomic model system seashore paspalum ( Paspalum vaginatum Swartz). To investigate how clonal propagation, ploidy variation, and interspecific hybridization vary across ecotypes and local salinity levels in wild P. vaginatum , we employed genotyping‐by‐sequencing, cpDNA sequencing and flow cytometry in 218 accessions representing > 170 wild collections from throughout the coastal southern United States plus USDA germplasm. We found that the two morphologically distinct ecotypes of P. vaginatum differ in their adaptive strategies. The fine‐textured ecotype is diploid and appears to reproduce in the wild both sexually and by clonal propagation; in contrast, the coarse‐textured ecotype consists largely of clonally‐propagating triploid and diploid genotypes. The coarse‐textured ecotype appears to be derived from hybridization between fine‐textured P. vaginatum and an unidentified Paspalum species. These clonally propagating hybrid genotypes are more broadly distributed than clonal fine‐textured genotypes and may represent a transition to a more generalist adaptive strategy. Additionally, the triploid genotypes vary in whether they carry one or two copies of the P. vaginatum subgenome, indicating multiple evolutionary origins. This variation in subgenome composition shows associations with local ocean salinity levels across the sampled populations and may play a role in local adaptation.

Fire tolerance of a resprouting Artemisia (Asteraceae) shrub - Stephen L. Winter; Samuel D. Fuhlendorf; Carla L. Goad; Craig A. Davis; Karen R. Hickman; David M. Leslie (Plant Ecology, 2011)